Is Your Child Safe Online? : A Parent's Guide to the Internet, Facebook, Mobile Phones & Other New Media - Whitby, Pamela (New Delhi Third Eye, 2012)
Is your child safe online? Do you know what information they access on a daily basis? The chances are that you are like most parents and the answer is 'no' or, at best, 'I'm not sure'. These days, our kids are more internet-savvy than we are - they know how to unblock privacy settings or get around simple parental controls. Yet more and more frequently there are stories in the news about children being victims of internet crime; whether through Facebook party invites, cyber-bullying or, worse, child grooming. But what can we do about it? As parents, we have a duty to understand the different media our children use and put in place boundaries and guidelines to protect them. Is Your Child Safe Online? has the practical advice you need to minimise the risk and ensure your child is protected today ... whilst still letting them do their homework. Covering all forms of new media - iPhones, apps, iPads, twitter, gaming online - as well as social networking sites - Is Your Child Safe Online? keeps you informed of the dangers and reassures with simple, straightforward advice. It arms you with practical methods to make sure your child is safe.
Include Glossary
Keywords: Internet--Access control -- Internet--Safety measures -- Internet and children